Drug Discovery for Cutaneous Leishmaniasis: A Review of Developments in the Past 15 Years - Hannah N. Corman; Case W. McNamara; Malina A. Bakowski (Microorganisms, 2023)
Leishmaniasis is a group of vector-borne, parasitic diseases caused by over 20 species of the protozoan Leishmania spp. The three major disease classifications, cutaneous, visceral, and mucocutaneous, have a range of clinical manifestations from self-healing skin lesions to hepatosplenomegaly and mucosal membrane damage to fatality. As a neglected tropical disease, leishmaniasis represents a major international health challenge, with nearly 350 million people living at risk of infection a year. The current chemotherapeutics used to treat leishmaniasis have harsh side effects, prolonged and costly treatment regimens, as well as emerging drug resistance, and are predominantly used for the treatment of visceral leishmaniasis. There is an undeniable need for the identification and development of novel chemotherapeutics targeting cutaneous leishmaniasis (CL), largely ignored by concerted drug development efforts. CL is mostly non-lethal and the most common presentation of this disease, with nearly 1 million new cases reported annually. Recognizing this unaddressed need, substantial yet fragmented progress in early drug discovery efforts for CL has occurred in the past 15 years and was outlined in this review. However, further work needs to be carried out to advance early discovery candidates towards the clinic. Importantly, there is a paucity of investment in the translation and development of therapies for CL, limiting the emergence of viable solutions to deal with this serious and complex international health problem.